Pengaruh Regret Aversion Bias dan Overconfidence terhadap Pengambilan Keputusan Investasi Cryptocurrency - Nursalimah, Ema; Utami, Indah; Panorama, Maya (Jurnal Manajemen Bisnis dan Keuangan, 2022)
This study aims to assess the effect of bias regret and overconfidence on cryptocurrency investment decision-making. The population in this study is investors from Sumatra, Java, and Nusa Tenggara (Bali) who have invested or only know about cryptocurrencies. The sampling technique of this study uses the objective sampling method for a population of 35 people. The method used in this study is a quantitative method using primers which were analyzed by path analysis using the SmartPLS 3.0 program. The results obtained in this study indicate that bias regret has no significant effect on investment decision-making, while overconfidence has a significant effect on investment decision-making.